2010
DOI: 10.1128/aac.00886-09
|View full text |Cite
|
Sign up to set email alerts
|

Ceftobiprole Is Superior to Vancomycin, Daptomycin, and Linezolid for Treatment of Experimental Endocarditis in Rabbits Caused by Methicillin-Resistant Staphylococcus aureus

Abstract: Beta lactam agents are the most active drugs for the treatment of streptococci and methicillin-susceptible Staphylococcus aureus endocarditis. However, methicillin-resistant S. aureus (MRSA) is resistant to all beta lactam agents licensed to date, and alternative treatments are limited. Ceftobiprole is a novel broad-spectrum cephalosporin that binds with high affinity to PBP 2a, the penicillin binding protein that mediates the methicillin resistance of staphylococci and is active against MRSA. Ceftobiprole was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Of note, ceftobiprole monotherapy was active when administered to animals at doses mimicking the treatment recommended in human (i.e., 500 mg b.i.d. ), thus confirming its intrinsic activity against VISA (4,15,45). On the other hand, it was not effective when used at low or very low doses, but these subtherapeutic doses could be Synergy between subtherapeutic doses of ceftobiprole and vancomycin against MRSA was also suggested in a recent meeting abstract (17).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Of note, ceftobiprole monotherapy was active when administered to animals at doses mimicking the treatment recommended in human (i.e., 500 mg b.i.d. ), thus confirming its intrinsic activity against VISA (4,15,45). On the other hand, it was not effective when used at low or very low doses, but these subtherapeutic doses could be Synergy between subtherapeutic doses of ceftobiprole and vancomycin against MRSA was also suggested in a recent meeting abstract (17).…”
Section: Discussionmentioning
confidence: 73%
“…Ceftobiprole is a novel broadspectrum cephalosporin with potent activity against Gram-positive pathogens, including MRSA and VISA (39), as well as Gram-negative pathogens. It has been reported to be efficacious in monotherapy against experimental endocarditis caused by both types of bacteria (4,15,45). It is therefore of interest to evaluate ceftobiprole as a potential partner with vancomycin for the treatment of endocarditis caused by MRSA or VISA.…”
mentioning
confidence: 99%
“…The numbers of CFU were counted to determine the tissue burdens of organisms. (8)(9)(10). The first dose of drug was administered 18 to 20 h after inoculation.…”
Section: Methodsmentioning
confidence: 99%
“…Endocarditis studies evaluating the activity of ceftaroline are very limited. However, Tattevin et al have assessed the activity of ceftobiprole (formerly BAL9141), the other anti-MRSA cephalosporin with high affinity for PBP2a, against MRSA in comparison with vancomycin, linezolid, and daptomycin (Tattevin et al, 2010). Using experimental conditions similar to the conditions used by Jacqueline et al, they showed that the burdens of organisms in vegetations were significantly lower in ceftobiprole-treated rabbits than in rabbits treated with vancomycin, linezolid, or daptomycin (4-day treatment) (Figure 13).…”
Section: Ceftaroline a Broad-spectrum Cephalosporin Active Against Mrsamentioning
confidence: 99%